Concept of Friedrich Nietzsche’s Apollonian and Dionysian and Its Influence on Aesthetic Dialogue in Two Stories by Maxim Gorky - M. M. Ozhigova (Научный диалог)
This article explores the implementation of Friedrich Nietzsche’s concept of the Apollonian and Dionysian in the works of M. Gorky. The aim of the study is to analyze the influence of Nietzsche’s ideas on Gorky’s aesthetic pursuits, both in his early and later works. The primary materials for this research are Gorky’s short story “On a Poet” (1894) and his text “Story About a Novel” (1924). The novelty of this study lies in the examination of a unique “dialogue” between these two works, which were written approximately thirty years apart. The focus of this “dialogue” is Gorky’s own aesthetic search and the impact of Nietzsche’s concept of the Apollonian and Dionysian on his development as a writer. The study provides a thorough analysis of both “On a Poet” and “Story About a Novel”, evaluating the extent to which the concept of the Apollonian and Dionysian is realized in these texts. It is shown that these works engage in a sort of “aesthetic dialogue”. The results of the study reveal direct quotations from Nietzsche’s treatise “The Birth of Tragedy” in Gorky’s texts, demonstrating the influence of Nietzsche ‘s ideas on Gorky’s views on the genesis of creativity and the questions of possibility and necessity in the creative process.